A Model for Talent Discovery and Recruitment Management in Banks Using Artificial Intelligence - Omidiparsa, Azar; Sheikholeslami Kandelousi, Nader (International journal of industrial engineering and operational research, 2023)
The importance of using artificial intelligence in human resource management is undeniable issue, and therefore, over time, most human resource managers will turn to using this technology, but the model of using artificial intelligence for talent discovery and hiring management is not yet clear for some organizations, and banks are no exception either. Therefore, in this research, a qualitative quantitative model had been designed for talent discovery and recruitment management in banks using artificial intelligence. At first, using literature review, 65 factors constituting talent discovery and hiring management were obtained, and then using Delphi technique, these 65 factors were reduced to 57 factors, then validation of related factors was done and it was shown that all factors in the banking content have credibility. Finally, nine main dimensions for talent discovery model and AI-based hiring management were identified in the banking industry, including cultural, human resources, and strategic managerial, individual, business, social, organizational and occupational dimensions.